DEVELOPING AND IMPLEMENTING A PHARMACY TECHNICIAN TRAINING PROGRAM ON EMERGENCY PREPAREDNESS: A COLLABORATIVE APPROACH - Mohammed Hussain A Almutairi, Ali Hasan M Almutairi, Ahmad Hussein Almutairi, Mounir Mukhaled Al-Mutairi, Abdulrahim Yahya Ahmed Asiri, Ahmed Hassan Aldawsari, (Chelonian Research Foundation, 2022)
Pharmacy technicians play a crucial role in maintaining medication supply and distribution during emergency situations. However, their training on emergency preparedness is often inadequate or inconsistent. This study aimed to develop and implement a comprehensive training program for pharmacy technicians on emergency preparedness through a collaborative approach involving multiple healthcare institutions in Hafar Al-Batin, Saudi Arabia. The training program was designed based on a needs assessment survey and expert panel recommendations, and consisted of online modules, in-person workshops, and simulation exercises. The program's effectiveness was evaluated using pre- and post-training assessments of knowledge, skills, and attitudes, as well as feedback from participants and stakeholders. The results showed significant improvements in participants' knowledge scores (from 60% to 85%, p<0.001), skills ratings (from 3.2 to 4.5 on a 5-point scale, p<0.001), and attitudes towards emergency preparedness (from 3.8 to 4.6 on a 5-point scale, p<0.001). The collaborative approach facilitated resource sharing, best practice exchange, and networking among pharmacy technicians from different institutions. This study provides a framework for developing and implementing a pharmacy technician training program on emergency preparedness that can be adapted to other healthcare settings and geographic regions.